2020
DOI: 10.1213/ane.0000000000005148
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Provides Cardioprotection During Early or Late Reperfusion Mediated by Different Mitochondrial K+-Channels

Abstract: Background: Cardioprotective interventions—such as pharmacological postconditioning—are a promising strategy to reduce deleterious consequences of ischemia and reperfusion injury (I/RI) in the heart, especially as timing and onset of myocardial infarction are unpredictable. Pharmacological postconditioning by treatment with dexmedetomidine (Dex), an α2-adrenoreceptor agonist, during reperfusion protects hearts from I/RI, independently of time point and duration of application during the reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“… 2 -adrenergic agonists are known to have a protective effect on myocardial ischemia by increasing cAMP levels and enhancing adenosine-induced coronary vasodilatation. Preconditioning with dexmedetomidine has been shown to attenuate myocardial ischemia/reperfusion injury by activating pro-survival kinases [ 19 , 20 ]. Both preconditioning and postconditioning with dexmedetomidine can therefore effectively protect the heart and brain from ischemia-reperfusion injury [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 -adrenergic agonists are known to have a protective effect on myocardial ischemia by increasing cAMP levels and enhancing adenosine-induced coronary vasodilatation. Preconditioning with dexmedetomidine has been shown to attenuate myocardial ischemia/reperfusion injury by activating pro-survival kinases [ 19 , 20 ]. Both preconditioning and postconditioning with dexmedetomidine can therefore effectively protect the heart and brain from ischemia-reperfusion injury [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…DEX is effective in attenuating the stress response to surgical stimulation and improving the oxygen supply-demand balance in the heart [25]. In addition, various studies have indicated that DEX exerts protective effects against I/R injury via direct action on the myocardium [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Postconditioning is considered to be a novel strategy to reduce myocardial damage during IR episodes (17, 18). Therefore, the present study aimed to explore the role of Eto postconditioning in MIRI rats.…”
Section: Introductionmentioning
confidence: 99%